A STUDY OF IFRS (INTERNATIONAL FINANCIAL REPORTING STANDARDS) AND ITS ADOPTION IN THE INDIAN BANKING SYSTEM - Maharshi, Aishwarya; Jadhav, Babasaheb (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The adoption of International Financial Reporting Standards (IFRS) represents a substantial step toward improving the comparability and transparency of financial reporting. This study looks at the role of a bank's International Financial Reporting Standards (IFRS) awareness and IFRS adoption levels on the financial reporting compliance of private banks in Pune City. A quantitative research methodology and a structured questionnaire for 85 financial managers were developed. Data was analysed using regression analysis and ANOVA. The study found that the greater awareness of IFRS by the financial managers positively contributes to higher compliance with IFRS (International Financial Reporting Standards). This study also determines that banks with high levels of IFRS adoption differ significantly in compliance when compared to banks with medium adoption levels and low IFRS adoption levels. The results highlight the valuable role of structured IFRS training and effective governance structure in improving reporting quality. Overall, based on the results of the study, the authors suggest that banks should emphasize ongoing training and education, improve audit committees' oversight of the subject matter, use technology to facilitate IFRS reporting, and a general commitment to training and supervision. In addition, commitment to a corporate culture of transparency and accountability from the Board and other top leaders is essential to effective IFRS implementation. Lastly, the study adds to the existing body of literature addressing IFRS adoption by the Indian banking sector and provides recommendations to improve compliance and transparency.